Предмет: Математика,
автор: 77010
)решите кто-нибудь умаляю очень срочно :(
Приложения:
Ответы
Автор ответа:
0
15+2(х+3у)=3(4х+у)
2(5х-у)-3у=2+3(2х-у)
15+2х+6у=12х+3у
10х-2у-3у=2+6х-3у
12х-2х+3у-6у=15
10х-6х - 2у=2
10х - 3у=15 ( *2)
4х - 2у=2 ( *-3)
20х-6у=30
- 12х+6у= -6
8х=24
х=3
х=3
4*3-2у=2
х=3
-2у=2-12
х=3
2у=10
х=3
у=5
(3;5)
2(5х-у)-3у=2+3(2х-у)
15+2х+6у=12х+3у
10х-2у-3у=2+6х-3у
12х-2х+3у-6у=15
10х-6х - 2у=2
10х - 3у=15 ( *2)
4х - 2у=2 ( *-3)
20х-6у=30
- 12х+6у= -6
8х=24
х=3
х=3
4*3-2у=2
х=3
-2у=2-12
х=3
2у=10
х=3
у=5
(3;5)
Похожие вопросы
Предмет: Оʻzbek tili,
автор: AMIRKAXXX
Предмет: Геометрия,
автор: заззазаз
Предмет: Английский язык,
автор: farizamurat
Предмет: Геометрия,
автор: kostyami